Analysis of Dietary Intake during Consecutive-Day Chemotherapy for Bone and Soft-Tissue Sarcomas - Hori, Yuta; Sakamoto, Akio; Goto, Takashi; Ando, Syouji; Yamashita, Manato; Shimomura, Masayo; Uemura, Takuji (Frontiers in Nutrition, 2018)
Background: Bone and soft tissue sarcomas are commonly treated with consecutive-day chemotherapy regimens consisting of multiple anticancer agents. Chemotherapy-induced nausea and vomiting (CINV) is a serious adverse effect of these regimens, and may result in decreased energy intake during chemotherapy. Decreased energy intake may lead to undernutrition and may cause adverse effects on patient quality of life and survival. Methods: Patients with bone and soft tissue sarcomas who received consecutive-day chemotherapy were retrospectively evaluated. CINV and dietary energy intake were assessed, as well as the occurrences of hiccups and constipation during chemotherapy. Results: A total of 13 patients, 10 males and 3 females, with a total 16 chemotherapy courses were included in the study. All patients received antiemetic prophylaxis. The CINV control rate, defined as no emesis and no rescue therapy, gradually decreased from chemotherapy day 1 (94%) to day 5 (75%). Four patients experienced emesis, 2 of whom had been treated with a cisplatin-containing regimen. Decreased dietary energy intake was possibly associated with CINV during chemotherapy. Anorexia was grade 2 except for one case of grade 3. The incidences of hiccups and constipation were high on days 3 to 5. Conclusion: Antiemetic prophylaxis treatment did not prevent emesis due to consecutive-day chemotherapy, especially with cisplatin-containing regimens, in patients with bone and soft-tissue tumors. Dietary energy intake decreased during chemotherapy, and this appeared to be associated with CINV. In addition, the incidence of hiccups and constipation increased during the course of consecutive-day chemotherapy regimens. Although these results are based on a small number of patients, it may be important to observe nutritional status during chemotherapy, as this may reflect a patient’s general condition. Nutritional counseling might be useful in supporting nutritional status in patients undergoing chemotherapy.